2011
DOI: 10.1007/978-3-642-22263-4_7
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate System-Wide Anonymity Metric for Probabilistic Attacks

Abstract: Abstract.We give a critical analysis of the system-wide anonymity metric of Edman et al. [3], which is based on the permanent value of a doubly-stochastic matrix. By providing an intuitive understanding of the permanent of such a matrix, we show that a metric that looks no further than this composite value is at best a rough indicator of anonymity. We identify situations where its inaccuracy is acute, and reveal a better anonymity indicator. Also, by constructing an information-preserving embedding of a smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Finally, Edman et al [30] propose a combinatorial anonymity metric that measures the amount of information needed to reveal the full set of relationships between the inputs and the outputs of a mix. Some extensions of this model were proposed by Gierlichs et al [31] and by Bagai et al [32].…”
Section: A Anonymous-communication Systems and Location-based Servicesmentioning
confidence: 98%
“…Finally, Edman et al [30] propose a combinatorial anonymity metric that measures the amount of information needed to reveal the full set of relationships between the inputs and the outputs of a mix. Some extensions of this model were proposed by Gierlichs et al [31] and by Bagai et al [32].…”
Section: A Anonymous-communication Systems and Location-based Servicesmentioning
confidence: 98%
“…Pseudonymity can be defined as the utilisation of an alias instead of personally identifiable information. A problem that can arise is the issue of Integrity [95]. The benefits include supporting user access to services without disclosing real identities.…”
Section: Privacy Preservation Through Access Patterns and Designmentioning
confidence: 99%
“…Similarly, in 2009, Grégoire and Hamel [119] extended the combinational approach proposed by Edman et al [117] to include the calculation information about how many messages were sent or received by a user and they define a new metric that can be computed exactly and efficiently using classical and elegant techniques from combinational enumeration. In 2011, Bagai et al [120] analyzed the system-wide anonymity metric of Edman and showed that while the metric for narrower class of infeasibility attacks is sound, the metric for probabilistic attacks has shortcomings. They then proposed a more accurate metric for both infeasible attacks and probabilistic attacks.…”
Section: Metrics Based On Combinatorial Mathsmentioning
confidence: 99%